(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: There is scarce evidence related to embedding physical activity in policy and practice at the local level. It is not enough to investigate only whether whole system approaches are effective; process evaluations are required to understand how and to assess the transferability of the intervention. This study examines the strategic-level mechanisms and contextual factors underpinning the success of the JU:MP whole system intervention, including understanding how and why the JU:MP whole system intervention worked and could work better. Methods: Participants included 86 stakeholders who contributed to the strategic-level design and delivery of JU:MP, including the core delivery and research team, the executive board, and stakeholders from organisations commissioned to lead on specific work streams. 55 focus groups, 57 interviews, and observation of 77 events (e.g. core meetings, stakeholder workshops) were conducted alongside intervention delivery periodically over five years (2019–2024). Data were analysed thematically using framework analysis. Results: Analysis revealed key areas of learning related to strategic-level design and delivery of JU:MP that influenced its success. For example, processes to ‘connect the system’ including regular community of learning events facilitated increased synergy and reduced tension across different JU:MP workstreams. A research-practice partnership approach was instrumental to facilitating evidence-based design, and continuous reflective practice informed iterative intervention improvement. Embedding capacity building and principles of equity and inclusion into different work streams, and commissioning processes, contributed to increased local buy-in and sustainable change. Contextual factors such as support from the funder and national evaluation team, and delivery organisation and financial processes, facilitated and constrained success in different ways. Conclusions: It is essential to evaluate the mechanisms underpinning local whole system approaches to physical activity across the United Kingdom and internationally. This study provides a blueprint that can guide these efforts, to enable more effective whole-system delivery and population-level increases in physical activity. Support/Funding source: This study was supported by Sport England’s Local Delivery Pilot – Bradford; weblink: https://www.sportengland.org/campaigns-and-our-work/local-delivery. Sport England is a non-departmental public body under the Department for Digital, Culture, Media and Sport. Keywords: Whole-system, partnership, capacity building, leadership, co-production